PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN APLIKASI RAKATA TERHADAP KETUNTASAN BELAJAR MENULIS TEKS PUISI SISWA KELAS X - Sri Silfiani; Ika Mustika; Enung Nurhayati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to analyze the effectiveness of the implementation of the Discovery Learning model assisted by the Rakata application on students' learning completion in writing poetry texts. The background of this study is based on the low ability to write poetry in class X students caused by the learning model that is less interesting and the minimal use of technology. An alternative solution to overcome this problem is to apply the Discovery Learning model which is designed to encourage students to be active in finding their own concepts, with the support of the Rakata application which allows creative and collaborative exploration in writing poetry. This study uses a quantitative approach with a pretest-posttest design. The subjects of the study were class X SMK students who were divided into experimental and control groups, each consisting of 30 students. The results showed that before the treatment, all students had not reached the Minimum Completion Criteria (KKM), with an average score of 47.56. After the implementation of the Discovery Learning model assisted by the Rakata application, there was a significant increase with an average score reaching 81.03 and classical completion of 70%. These findings indicate that learning models combined with technology can improve poetry writing skills effectively.